Carbon dioxide hydrogenation to aromatic hydrocarbons by using an iron/iron oxide nanocatalyst - Wang, Hongwang; Hodgson, Jim; Shrestha, Tej B.; Thapa, Prem S.; Moore, David; Wu, Xiaorong; Ikenberry, Myles; Troyer, Deryl L.; Wang, Donghai; Hohn, Keith L.; Bossmann, Stefan H. (Beilstein Journal of Nanotechnology, 2014)
The quest for renewable and cleaner energy sources to meet the rapid population and economic growth is more urgent than ever before. Being the most abundant carbon source in the atmosphere of Earth, CO2 can be used as an inexpensive C1 building block in the synthesis of aromatic fuels for internal combustion engines. We designed a process capable of synthesizing benzene, toluene, xylenes and mesitylene from CO2 and H2 at modest temperatures (T = 380 to 540 °C) employing Fe/Fe3O4 nanoparticles as catalyst. The synthesis of the catalyst and the mechanism of CO2-hydrogenation will be discussed, as well as further applications of Fe/Fe3O4 nanoparticles in catalysis.
Keywords: aromatic hydrocarbons; carbon dioxide reduction; heterogenous catalysis; iron/iron oxide nanocatalyst